2018
DOI: 10.5334/gjgl.436
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical versus lexical words in theory and aphasia: Integrating linguistics and neurolinguistics

Abstract: The distinction between grammatical and lexical words is standardly dealt with in terms of a semantic distinction between function and content words or in terms of distributional distinctions between closed and open classes. This paper argues that such distinctions fall short in several respects, and that the grammar-lexicon distinction applies even within the same word class. The argument is based on a recent functional and usage-based theory of the grammar-lexicon distinction (Boye & Harder 2012) and on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
2
25
0
1
Order By: Relevance
“…Specifically, pIFG may be involved in the phonological aspects of grammatical processing, whereas aIFG may be responsible for processing semantic information of grammatical and lexical items. Using the same behavioral paradigm, in both healthy subjects and agrammatic patients, our group found converging evidence that grammatical items are processed differently from lexical items (Ishkhanyan et al, 2017(Ishkhanyan et al, , 2019Michel Lange et al, 2017Boye and Bastiaanse, 2018;Nielsen et al, 2019). Together, the results encourage future research into the joint contributions of frontal and parietotemporal brain regions to these processes during language production.…”
Section: Discussionsupporting
confidence: 52%
“…Specifically, pIFG may be involved in the phonological aspects of grammatical processing, whereas aIFG may be responsible for processing semantic information of grammatical and lexical items. Using the same behavioral paradigm, in both healthy subjects and agrammatic patients, our group found converging evidence that grammatical items are processed differently from lexical items (Ishkhanyan et al, 2017(Ishkhanyan et al, , 2019Michel Lange et al, 2017Boye and Bastiaanse, 2018;Nielsen et al, 2019). Together, the results encourage future research into the joint contributions of frontal and parietotemporal brain regions to these processes during language production.…”
Section: Discussionsupporting
confidence: 52%
“…The theory is supported by both psycholinguistic and neurolinguistic data. For example, it has been shown that individuals with agrammatic aphasia (a grammatical impairment after brain damage) have more problems producing verbs classified as 'grammatical' than verbs classified as 'lexical' (Boye & Bastiaanse, 2018). Similar results have been reported for French agrammatic speakers (Ishkhanyan et al, 2017).…”
Section: Time Reference Through Verb Inflection and Aspectual Adverbs Comparedsupporting
confidence: 61%
“…A usage-based linguistic theory adopted by several recent studies on aphasia (e.g., Boye & Bastiaanse, 2018;Ishkhanyan et al, 2017;Martínez-Ferreiro et al, 2019;Nielsen et al, 2019) has been developed by Boye and Harder (2012). In particular, Boye and Harder proposed a functional theory of grammatical status, which provided a theoretical anchor for the grammar-lexicon contrast.…”
Section: Linguistic Usage-based Theories and Aphasia Researchmentioning
confidence: 99%
“…Importantly, applying these diagnostic criteria sometimes result in classifications that challenge established views in that (1) word classes such as prepositions and pronouns are not treated as homogenous (see Boye & Harder, 2012;Ishkhanyan et al, 2017), and (2) the resultant classifications of words into lexical and grammatical items cut across distinctions between content and function words or between open-class and closedclass words. Boye and Harder's (2012) functional theory has gained empirical support from studies on aphasia (e.g., Boye & Bastiaanse, 2018;Ishkhanyan et al, 2017;Martínez-Ferreiro et al, 2019;Nielsen et al, 2019) and at the same time provided a theoretical framework that, according to its proponents, allows a precise characterization of the linguistic deficits attested in non-fluent and fluent aphasia.…”
Section: Linguistic Usage-based Theories and Aphasia Researchmentioning
confidence: 99%
See 1 more Smart Citation